Principal Management in Building a Religious School Culture based on Islamic Values - Dewi, Fetty Kurnia (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Developing an Islamic school culture is essential for shaping students' character and integrating Islamic values into the educational environment. The role of the principal is crucial in managing and sustaining this culture through strategic planning and leadership. Objective: This study aims to analyze the principal's management in fostering an Islamic school culture at SMPN 5 Kota Bengkulu. It focuses on the planning, implementation, opportunities, challenges, and evaluation of Islamic cultural activities within the school. Method: The research employs a qualitative approach using a case study method. Data were gathered from principals, teachers, staff, and students through observation, interviews, and documentation. The data were analyzed descriptively using data reduction, data display, and conclusion drawing to identify management patterns. Result: The findings reveal that the principal’s management of Islamic school culture involves both short-term and long-term planning. Implementation includes structured activities without formal written assessments, except during competitions. Students receive rewards such as money, certificates, and extracurricular points, while sanctions are applied to those who violate school rules. Conclusion: The study concludes that while the principal’s management supports Islamic cultural development, there is room for improvement in assessment methods and consistency in reinforcement strategies. Management efforts must be aligned with the goal of instilling Islamic values as daily habits. Contribution: This research contributes practical insights for school leaders in optimizing the principal’s role in Islamic school culture development. It also offers recommendations for more effective management strategies to integrate Islamic values into the school’s operational and cultural framework.